Recurrent anterior shoulder dislocation with glenoid fracture managed by modified Boytchev procedure: a rare case report - Devgan, Ashish; Yadav, Umesh; Rohilla, Rajesh; Sharma, Pankaj; Goel, Varun; Mudgil, Parvesh; Singh, Sujit Kumar; Verma, Aman; Ranjan, Karunesh; Dhupper, Vasudha (International Journal of Research in Orthopaedics, 2019)
Surgical procedures for recurrent anterior dislocation of the shoulder include using capsuloligamentous or bone blocks to create barriers and active interventions using muscle actions. Fracture of glenoid acts as a barrier for bone block procedures. Boytchev procedure, though outmoded, yet acts as simple and effective procedure in this condition. Here we report a 44 year old male with recurrent anterior dislocation with glenoid fracture treated by Boytchev procedure. The patient is on regular follow up since 3 years with no episode of shoulder dislocation till now with full range of movements. To conclude, Boytchev procedure is technically simple and effective method in patients with recurrent anterior shoulder dislocation with fracture of glenoid.